Analysis Of Fixed Mobile Convergence (FMC) Product Launch On Telecommunication Stock Returns In Indonesia - Salim, Dwi Fitrizal; Heryanto, Ari; Kristanti, Farida Titik; Beshr, Baligh Ali Hasan; Riyadh, Hosam Alden (Journal of Ecohumanism, 2024)
This research evaluates the possibility of a Fixed-Mobile Convergence (FMC) strategy in the telecommunications sector, particularly in light of the significant increase in data consumption globally. Based on a report from Ericsson Mobility and market analysis, FMC services are expected to contribute around 10-20% to the total revenue of telecommunications companies. The success of this strategy in Western Europe and the vast potential in the Asia Pacific region, including Indonesia, confirm this. This study is conducted using a comparative descriptive method on the stock returns of FMC players in Indonesia, thus aiming to prove whether FMC events can affect the dynamics of the telecommunications market in Indonesia and enrich investors’ understanding of the potential of FMC on the financial performance of telecommunications companies, this can subsequently be manifested in the market’s stock performance of telecoms business. The importance of analyzing changes in stock returns for investors of FMC operators in Indonesia, such as XL, SmartFren, and Telkomsel, both before and after the launch of FMC products, is a particular focus. In this case, the paired t-test and Wilcoxon Signed Rank Test methods assess significant differences between the means of two paired samples. The findings of this study offer practical guidance for investors looking at FMC strategies as information for making more informed investment decisions and improving their portfolio performance.